Kapasistas Transformasi Alur Kerja Konvensional Menuju Digital Office di Pemerintah Desa Puloniti Kecamatan Bangsal Kabupaten Mojokerto (International Forum of Researchers and Lecturers, 2025)
The advancement of digitalization and government programs through the Electronic-Based Government System (SPBE) have impacted digital performance systems at various levels of government. The Puloniti village government is also one of the village governments that needs to transform conventional performance into digital performance in response to global challenges. Through this study, the research team aims to assess the capacity of the Puloniti village government to carry out digital work transformation and identify the main obstacles that hinder it. This research was conducted using a qualitative descriptive approach through observation, interviews, and documentation. This study identified two main obstacles for the Puloniti village government in carrying out digital performance transformation: limited human resource literacy and inadequate software facilities and infrastructure.